Brand trust and brand loyalty in electronics home appliances in Bangladesh: moderating role of demography and brand-origin, social media and its usage duration - Uzir, Md Uzir Hossain; Bukari, Zakari; Abdul Hamid, Abu Bakar; Abdul Latiff, Ahmad Shaharudin; Haque, A. K. M. Ahasanul (Inderscience Enterprises Ltd., 2025)
The objective of the study is to inspect brand loyalty and its predictors in electronics home appliances (EHAs) considering social media usage, brand trust and demography effects in their relationships. Design: The study was conducted in Dhaka, Bangladesh, with 486 respondents using a structured questionnaire with a mall-intercept sampling. Collected data were analysed in statistical package for social socience (SPSS), and partial least square-structural equation modelling (PLS-SEM). Findings: The findings revealed customer satisfaction and brand awareness have an effect on brand trust; and brand trust is an influencer on brand loyalty. Contrarily, brand experience and brand image are insignificant with respect to brand trust as social media usage and respondent demography do not moderate the relationship. Implications: The findings contribute to the Stimulus-Organism- Response (S-O-R) theory. The practicing managers could make an effort to increase trust among EHA users. Originality and Value: The study is one of the first studies conducted on EHAs investigating the effect on brand trust on brand loyalty.